Expression of acid phosphatase in the seminiferous epithelium of vertebrates - Peruquetti, R. L. [UNESP]; Taboga, S. R. [UNESP]; Oliveira, Maria Tercília Vilela de Azeredo [UNESP] (Genetics and Molecular Research, 2010)
Acid phosphatases (AcPs) are known to provide phosphate to tissues that have high energy requirements, especially during development, growth and maturation. During spermatogenesis AcP activity is manifested in heterophagous lysosomes of Sertoli cells. This phagocytic function appears to be hormone-independent. We examined the expression pattern of AcP during the reproductive period of four species belonging to different vertebrate groups: Tilapia rendalli (Teleostei, Cichlidae), Dendropsophus minutus (Amphibia, Anura), Meriones unguiculatus (Mammalia, Rodentia), and Oryctolagus cuniculus (Mammalia, Lagomorpha). To demonstrate AcP activity, cryosections were processed for enzyme histochemistry by a modification of the method of Gömöri. AcP activity was similar in the testes of these four species. Testes of T. rendalli, D. minutus and M. unguiculatus showed an intense reaction in the Sertoli cell region. AcP activity was detected in the testes of D. minutus and O. cuniculus in seminiferous epithelium regions, where cells are found in more advanced stages of development. The seminiferous epithelium of all four species exhibited AcP activity, mainly in the cytoplasm of either Sertoli cells or germ cells. These findings reinforce the importance of AcP activity during the spermatogenesis process in vertebrates. © FUNPEC-RP.
Keywords: Acid phosphatase; Reproduction; Spermatogenesis; Testis; Vertebrates; acid phosphatase; Amphibia; animal tissue; cell maturation; controlled study; Dendropsophus minutus; enzyme activity; enzyme histochemistry; fish; germ cell; male; mammal; meriones unguiculatus; nonhuman; Oryctolagus cuniculus; protein expression; reproduction; seminiferous tubule epithelium; Sertoli cell; spermatogenesis; testis; Tilapia rendalli; vertebrate; Acid Phosphatase; Animals; Male; Seminiferous Epithelium; Anura; Cichlidae; Hyla minuta; Lagomorpha; Mammalia; Meriones unguiculatus; Rodentia; Teleostei; Vertebrata